2010
DOI: 10.1038/hdy.2010.32
|View full text |Cite
|
Sign up to set email alerts
|

Low genetic differentiation in a sedentary bird: house sparrow population genetics in a contiguous landscape

Abstract: The house sparrow Passer domesticus has been declining in abundance in many localities, including Finland. We studied the genetic diversity and differentiation of the house sparrow populations across Finland in the 1980s, at the onset of the species' decline in abundance. We genotyped 472 adult males (the less dispersive sex) from 13 locations in Finland (covering a range of 400 Â 800 km) and one in Sweden (Stockholm) for 13 polymorphic microsatellite markers. Our analysis of Finnish ringing records showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
70
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 55 publications
4
70
2
Order By: Relevance
“…It is also striking that these estimates are comparable to those found at the scale of much larger regions in other passerines such as the House Sparrow (Passer domesticus) (F ST ¼ 0.004 across Finland; Kekkonen et al, 2011) or the Eurasian Reed Warblers (Acrocephalus scirpaceus) Procházka et al, 2011). Thus, we suggest that the levels of genetic differentiation found in our study are not just unexpected, they are exceptionally high for birds at such a small spatial scale.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…It is also striking that these estimates are comparable to those found at the scale of much larger regions in other passerines such as the House Sparrow (Passer domesticus) (F ST ¼ 0.004 across Finland; Kekkonen et al, 2011) or the Eurasian Reed Warblers (Acrocephalus scirpaceus) Procházka et al, 2011). Thus, we suggest that the levels of genetic differentiation found in our study are not just unexpected, they are exceptionally high for birds at such a small spatial scale.…”
supporting
confidence: 69%
“…Although many empirical studies provide support to this idea, with low or non-significant differentiation found even in bird species distributed over a broad geographic scale (Kekkonen et al, 2011;Procházka et al, 2011, for some recent examples), there are also a few striking cases of phenotypic and genetic differentiation among passerine and some other bird populations at relatively small spatial scales (for example, De Léon et al, 2010;Milá et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This view, however, was challenged by Heij (1985) who concluded that both urban and rural study populations were highly dependent on suburban immigrants for their long-term viability. Several other studies also failed to reveal (large) genetic dissimilarities between house sparrow populations in the absence of strong geographical barriers (Fleisher, 1983;Parkin and Cole, 1984;Kekkonen et al, 2010). Yet, all these studies had in common that they described dispersal and/or genetic structure well before the onset of the population decline.…”
Section: Introductionmentioning
confidence: 99%
“…Local extinction without recolonization may transform contiguous populations into patchy ones, a pattern currently (mainly) observed in urban areas (Shaw et al, 2008;Vangestel, 2011). As house sparrows most likely (used to) disperse according to a stepwise pattern (Kekkonen et al, 2010), loss of intermediate 'stepping-stones' combined with the intrinsic sedentary nature of house sparrows (Anderson, 2006) may have reduced or even inhibited contemporary dispersal between adjacent colonies (Hole, 2001). Hole (2001) was among the first to suggest that such loss of (intermediate) populations may gradually increase distances between remaining source-sink populations up to a point at which house sparrow metapopulation dynamics become constrained and populations genetically diverge, ultimately resulting in an extinction vortex that spreads through the landscape.…”
Section: Introductionmentioning
confidence: 99%
“…Such philopatric behavior may result in local extinctions not being compensated by recolonization, and hence may transform contiguous populations into patchy ones-a pattern currently observed in highly built-up areas (Shaw et al, 2008;Vangestel et al, 2011). Despite this highly sedentary behavior of house sparrows, several studies failed to detect large-scale genetic differentiation in the absence of geographical barriers (Fleischer, 1983;Parkin and Cole, 1984;Kekkonen et al, 2011b; but see Jensen et al, 2013 for the island effect), even after a severe population decline (Kekkonen et al, 2011a;Schrey et al, 2011). This lack of differentiation may be explained by the fact that even few individuals dispersing in a stepping-stone pattern already suffice to maintain genetic homogeneity across large geographic distances (Allendorf, 1983).…”
Section: Introductionmentioning
confidence: 99%